Interação entre IQGAP1 e actina mediado por CDC42 e RAC1 - Pereira, Rafael Luzes (2010)
IQGAP1 stimulates branched actin filament nucleation by activating N-WASP, which in turn activates the Arp2/3 complex. N-WASP can be activated by other factors, including GTP-bound forms of Cdc42 and Rac1, which also bind IQGAP1. We report here the use of purified proteins for in vitro binding and actin polymerization assays, and of fluorescence resonance energy transfer (FRET) microscopy of cultured cells to illuminate functional interactions involving IQGAP1, N-WASP, and either Cdc42 or Rac1. In pyrene-actin assembly assays in the presence of N-WASP and the Arp2/3 complex, Cdc42 and IQGAP1 cooperatively stimulated actin filament nucleation, primarily by reducing the lag time before assembly Vmax was reached. Cooperativity reflected dose-dependent stimulation by Cdc42 of IQGAP1 binding to N-WASP. Rac1 and IQGAP1 behaved differently. At low Rac1, the two proteins cooperatively reduced the lag time before assembly Vmax was reached, but at high Rac1 Vmax was faster and reached more quickly for Rac1 alone than for either IQGAP1 alone, or the combination of Rac1 and IQGAP1. This negative cooperativity reflected dose-dependent inhibition by Rac1 of IQGAP1 binding to N-WASP. These results suggest that IQGAP1 interacts by distinct mechanisms with Cdc42 versus Rac1 to regulate actin filament assembly through N-WASP in vivo. To address this possibility, FRET microscopy was used to study interactions of GFP-IQGAP1 with mOrange-Cdc42 versus mOrange-Rac1 in live MDCK cells. Robust FRET was observed for both donor/acceptor pairs at F-actin rich cell-cell margins, but the average intermolecular FRET distances closer for IQGAP1-Cdc42 than for IQGAP1-Rac1. The distinct interactions of IQGAP1 with Cdc42 versus Rac1 observed in vitro were thus recapitulated in live cells.